Harnessing the Power of Social Media for Wildlife Rehabilitation - Nicholson, Amanda (Wildlife Rehabilitation Bulletin, 2021)
In today’s digital age, social media plays a significant role in both personal and professional lives. Many wildlife rehabilitation centers and organizations have joined the social media landscape in some way, but still are learning how to navigate in this complex online environment. Learning how to effectively use and harness the power of social media is a valuable tool for connecting and engaging with supporters.